Moving to density: Half a century of housing costs and wage premia from Queens to King Salmon - Stan Veuger; Philip G. Hoxie; Daniel Shoag (American Enterprise Institute (AEI), 2023)
Have workers stopped moving to the highest-density, highest-productivity places in the country because of a decline in the urban wage premium, or because the rent is too high?
Keywords: A; 330; Density; Housing; Migration; Skills; Wages